A Study on the Transmission Line in FBAR Duplexer for Industrial Wireless Communication in the Context of Industry 4.0 - Lee, EunKyu; Joong Kim, Jae; Rim Choi, Hyung; Hyeok Lim, Cheong; Hoon Cha, Sang (International Journal of Engineering and Technology, 2018)
Background/Objectives: This paper designs and manufactures a transmission line with PCB stacking of 3.8mm x 3.8mm x 1.8mm for the miniaturization of FBAR duplexer.Methods/Statistical analysis: To evaluate the performance of the fabricated transmission line, we applied it to a duplexer made up of Tx and Rx filters made of a combination of FBAR resonators and confirmed its characteristics.Findings: In this study, a pentagonal resonator was fabricated for each filter size, and Tx and Rx filters were designed after extracting physical properties for each resonator. And we design duplexer using combined Tx/Rx filter. The characteristics of the transmission line were analyzed by using the designed duplexer.Improvements/Applications: The line width of the transmission applied to the duplexer was 210ãŽ› and designed as a strip line having a length of 18mm.It was confirmed that the phase difference was 179.9Â° at 18mm.A transmission line was applied to a very small FBAR duplexer having a size of 3.8 mmÃ—(length) 3.8 mmÃ—(height) 1.8 mm to be applied (width) to obtain S11 (-5.638 dB), S21 (-18.296 dB), S31 42.832dB).Â